Catalytic conversion of waste corrugated cardboard into lactic acid using lanthanide triflates. (1st May 2022) - Kim, Kwang Ho; Jin, Xuanjun; Ji, Anqi; Aui, Alvina; Mba-Wright, Mark; Yoo, Chun-Jae; Choi, Jae-Wook; Ha, Jeong-Myeong; Kim, Chang Soo; Yoo, Chang Geun; Choi, Joon Weon
Highlights: A waste valorization approach is proposed to achieve a sustainable bioeconomy. Lanthanide triflates are highly effective to convert paper wastes into lactic acid. Chemocatalytic conversion strategy was found to be economically feasible. Paper wastes can serve as important feedstock for high-value coproduct stream. Abstract: The efficient strategy for waste conversion and resource recovery is of great interest in the sustainable bioeconomy context. This work reports on the catalytic upcycling of waste corrugated cardboard (WCC) into lactic acid using lanthanide triflates catalysts. WCC, a primary contributor to municipal solid wastes, has been viewed as a feedstock for producing a wide range of renewable products. Hydrothermal conversion of WCC was carried out in the presence of several lanthanide triflates. The reaction with erbium(III) triflate (Er(OTf)3 ) and ytterbium(III) triflate (Yb(OTf)3 ) resulted in high lactic acid yields, 65.5 and 64.3 mol%, respectively. In addition, various monomeric phenols were readily obtained as a co-product stream, opening up opportunities in waste management and resource recovery. Finally, technoeconomic analysis was conducted based on the experimental results, which suggests a significant economic benefit of chemocatalytic upcycling of WCC into lactic acid.